The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12864-015-1690-2
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila anti-nematode and antibacterial immune regulators revealed by RNA-Seq

Abstract: BackgroundDrosophila melanogaster activates a variety of immune responses against microbial infections. However, information on the Drosophila immune response to entomopathogenic nematode infections is currently limited. The nematode Heterorhabditis bacteriophora is an insect parasite that forms a mutualistic relationship with the gram-negative bacteria Photorhabdus luminescens. Following infection, the nematodes release the bacteria that quickly multiply within the insect and produce several toxins that event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 100 publications
(101 reference statements)
1
60
0
1
Order By: Relevance
“…HSP70  has vital housekeeping functions, maintaining homeostasis and protecting cells against thermal and oxidative stress [57] and was up-regulated in Culex larvae whether they had been infected with blastospores or conidia suggesting that HSP70 played a key role in stress management in mosquito larvae. Castillo et al [58] found that up-regulation of HSP genes is evidence of increasing stress in response to pathogen infection. In this study, HSP70 in Culex larvae infected with conidia, was expressed earlier and to a greater extent than in larvae infected with blastospores, which up regulated this gene at 48 hr pi.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70  has vital housekeeping functions, maintaining homeostasis and protecting cells against thermal and oxidative stress [57] and was up-regulated in Culex larvae whether they had been infected with blastospores or conidia suggesting that HSP70 played a key role in stress management in mosquito larvae. Castillo et al [58] found that up-regulation of HSP genes is evidence of increasing stress in response to pathogen infection. In this study, HSP70 in Culex larvae infected with conidia, was expressed earlier and to a greater extent than in larvae infected with blastospores, which up regulated this gene at 48 hr pi.…”
Section: Discussionmentioning
confidence: 99%
“…Huge numbers of transcriptomes were analyzed at the whole-genome level by means of microarray. Whole-genome mRNA sequencing (RNA-Seq) technologies have been a significant advance for high-throughput transcriptome analyses, as they can generate hundreds of millions reads in a single sequencing run (Castillo et al, 2015;Ozsolak and Milos, 2011;Wang et al, 2009). This is more sensitive, quantitative and efficient, and it has higher reproducibility compared to previously use hybridizationbased microarray techniques (Castillo et al, 2015;de Klerk et al, 2014).…”
Section: Rna Sequencing and Data Analysismentioning
confidence: 99%
“…Whole-genome mRNA sequencing (RNA-Seq) technologies have been a significant advance for high-throughput transcriptome analyses, as they can generate hundreds of millions reads in a single sequencing run (Castillo et al, 2015;Ozsolak and Milos, 2011;Wang et al, 2009). This is more sensitive, quantitative and efficient, and it has higher reproducibility compared to previously use hybridizationbased microarray techniques (Castillo et al, 2015;de Klerk et al, 2014). RNA-Seq has already produced exciting and novel information in the study of various diseases (Costa et al, 2013;Castillo et al, 2015;Xuan et al, 2013).…”
Section: Rna Sequencing and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations